Prediction of insulin resistance in late adolescent based on anthropometric index - Fitriyanti, Addina Rizky; Sulchan, Muhammad; Tjahjono, Kusmiyati; Sunarto, Sunarto (Jurnal Gizi dan Pangan, 2019)
The study aimed to evaluate the role of neck circumference for predicting insulin resistance in adolescent compared with waist circumference and waist hip ratio. A cross sectional study was conducted by measuring anthropometric parameters (neck circumference, waist circumference, hip circumference) and biochemical parameter (fasting plasma glucose, fasting insulin, and HOMA-IR) involving 80 late adolescents. Statistical analysis used in this study were Pearson and Spearman correlation, multivariate linear regression. Neck circumference positively correlated with fasting insulin and HOMA-IR in both gender, while neck circumference only positively correlated with fasting plasma glucose in men. In addition, multivariate linier regression showed that a higher regression coefficient of waist circumference associated with a higher risk of insulin resistance (fasting insulin (β=0.11; p<0.05), HOMA-IR (β=0.05; p<0.05)) compared to neck circumference and waist hip ratio. Neck circumference, waist circumference, and waist hip ratio is an anthropometry indicators that could be used to predict insulin resistance.  However, waist circumference is better than neck circumference and waist hip ratio for predicting insulin resistance in adolescent.